Highly efficient spin injection and readout across Van Der Waals interface - Chen, Hao (2024)
Spin injection, transport, and detection across the interface between a ferromagnet and a spin-carrying channel are crucial for energy-efficient spin logic devices. However, interfacial conductance mismatch, spin dephasing, and inefficient spin-to-charge conversion significantly reduce the efficiency of these processes. In this study, it is demonstrated that an all van der Waals heterostructure consisting of a ferromagnet (Fe3GeTe2) and Weyl semimetal enables a large spin readout efficiency. Specifically, a nonlocal spin readout signal of 150 mΩ and a local spin readout signal of 7.8 Ω is achieved, which reach the signal level useful for practical spintronic devices. The remarkable spin readout signal is attributed to suppressed spin dephasing channels at the vdW interfaces, long spin diffusion, and efficient charge-spin interconversion in Td-MoTe2. These findings highlight the potential of vdW heterostructures for spin Hall effect-enabled spin detection with high efficiency, opening up new possibilities for spin-orbit logic devices using vdW interfaces.